Implementation of Sanctions Against Unlicensed Alcoholic Beverage Sellers in Pekanbaru City Based on Regional Government Regulation No. 13 of 2021 concerning Public Order and Tranquility - Al Qudri; Ardiansyah; Bagio Kadaryanto (Magister Ilmu Hukum Fakultas Hukum Universitas Riau, 2023)
This study aims to examine the efforts of Satpol PP as the enforcer of Perda and Perkada in tackling the circulation of alcoholic beverages and the application of sanctions against its sellers in Pekanbaru city as well as the factors that support and inhibit the enforcement of the Law. The research method used is field research method, the research was conducted in pekanbaru city. The type of research in this writing is empirical juridical research, because it approaches the problem from the applicable regulations and the reality in society. the results of this study There are 3 (three) efforts of Satpol pp and related agencies in tackling the circulation of alcoholic beverages, namely: Preincentive efforts, preventive efforts and repressive efforts in this case Satpol PP and related agencies have 3 (three) supporting factors, namely: legal substance factors, informant factors, community leaders factors. and 4 (four) inhibiting factors, namely: human resource factors, intellectual resources of expert investigators, facilities and infrastructure factors of law enforcement, ground rules factors, community factors, and community culture factors.